TINJAUAN ANALISIS PERBANDINGAN KEKUATAN, KEKAKUAN, STABILITAS BEKISTING KONVENSIONAL DENGAN FIBERGLASS - Telly Rosdiyani; Euis Amilia; Muhammad Affandi Abdullah (Jurnal Sipil Krisna, 2023)
In the construction of the new classroom building of madrasah Tsanawiyah Negeri 5 Lebak, Banten Province, of course, there is a formwork. The formwork used is made of multiplek wood and beam wood. Along with the development of technological advances, especially in the application of concrete printers or formwork, fiberglass formwork made of plastic was created. Fiberglass formwork has several advantages over conventional formwork including that it does not require a lot of labor and can also reduce waste waste left over from concrete casting (wood and boards The purpose of this study was to determine the implementation of work on column structures and floor plates in classroom construction projects reviewed against strength, rigidity and stability, and be able to compare the use of conventional formwork with fiberglass formwork. The required data consists of primary data and skunder data, primary data is obtained directly conducting interviews with related parties while skunder data is in the form of maps, specs, time schedules, and images The results of the comparison deviation of the two types of formwork in terms of strength there was a weight difference of 32.5 kg / cm2, the stiffness was 0.087 cm. Furthermore, in the calculation results of the strength of the floor slab structure, there are 1.98 kg / cm, rigidity 0.018 cm. Then the calculation of the control of the weight placement reaction of 1902.04 kg.and the latitude force of 1056.69 kg and the control of scaffolding 1611.55 kg / cm2